A Conjoint Analysis of Cooperative Savings Product Preferences Among Generation Z College Students in Davao City - Sumatra, Emmanuel Joseph B. (Journal of Interdisciplinary Socio-Economic and Community Study, 2023)
Limited marketing hinders cooperatives' ability to attract and retain members, particularly younger generations like Generation Z. This study investigates the financial preferences of Gen Z students within the cooperative context, focusing on their preferred savings products. Using a conjoint analysis of 664 participants from three Davao City universities, this paper reveals insights into this demographic's financial decision-making processes. The data shows the paramount importance of promotion in influencing Gen Z's financial choices. Efficient social media campaigns emphasizing a positive and engaging cooperative identity significantly resonate with these young adults. While convenience, like proximity to public areas, is valued, it holds less weight compared to competitive interest rates and impactful promotional strategies. These findings offer actionable recommendations for cooperatives aiming to engage Gen Z. Aligning marketing strategies with their preferred channels and messages, tailoring product offerings to prioritize competitive rates and engaging social media presence, and fostering community engagement through educational partnerships are crucial steps toward success. The implications extend beyond Davao City, providing a framework for cooperatives in developing countries to effectively engage young adults. By understanding Gen Z's unique financial preferences and leveraging this knowledge to develop targeted marketing and product offerings, cooperatives can contribute to financial inclusion and position themselves as vital partners in building a financially empowered future for this generation. This study's multi-theoretical framework paves the way for future research and initiatives aimed at promoting financial literacy and community engagement programs tailored to resonate with Gen Z.